Influencia de los abonos organicos sobre las propiedades de los suelos en el cultivo de maiz (Zea mays L.) - Garcia Vera, Gualberto Alexander (2019)
SUMMARY This practical work was carried out in the Faculty of Agricultural Sciences of the Technical University of Babahoyo, for the elaboration of the document information was collected from books, journals, scientific articles that were summarized in this document on the influence of organic fertilizers in the properties of soils in the cultivation of corn. From the information gathered it was determined that since a few years ago, since the "Green Revolution", excessive use of chemical fertilizers, pesticides, machinery, among others, has been implemented, which has solved the problem of food loss, but has produced losses in the quality of the soils and contamination to the forms of life found inside. For what is nowadays to return to a sustainable use of resources and the implementation of organic fertilizers is considered as an alternative. So it is concluded that organic fertilizers condition the soil and improve its physical, chemical and biological characteristics by improving and increasing the beneficial microorganisms of the soil, managing to provide nutrients necessary for the development and production of crops. Abstract: Organic Fertilizers, Fertility, Soil Properties, Microorganism.